Detection and mapping of cold-water coral mounds and living Lophelia reefs in the Galicia Bank, Atlantic NW Iberia margin - Somoza, Luis; Ercilla, Gemma; Urgorri, V.; León Buendía, Ricardo F.; Medialdea Cela, Teresa; Paredes, Manuel; González Sanz, Francisco Javier; Nombela, Miguel Ángel (Marine Geology, 2014)
18 pages, 14 figures We report, for first time, the occurrence of cold-water coral mounds and large number of living Lophelia reefs along the Galicia Bank (Atlantic NW Iberian margin). Detection and mapping of living coral reefs and mounds have been carried out by means of multibeam bathymetry, backscatter images, ultra-high resolution and high-resolution multichannel seismic reflection data and sampling. In addition, profiling CTDs have been made to characterise environmental conditions as temperature, salinity and dissolved oxygen contents of the coral sites. Based on these dataset, two main provinces of cold-water coral mounds and reefs have been identified in the Galicia Bank at water depths between 620 and 1125. m. The Breogham Mound Province along the western flank of the Galicia Bank shows a sequence of well-developed mounds composed of: (1) Stepped semi-buried elongated mounds, the tallest mounds with heights up 70. m and widths of 450. m lined up in along-slope trending ridges and intercalated with upslope migrating sediment drifts at water depths from 1125 to 826. m; (2) Single and composite seabed mounds show heights of 10-12. m and average widths of 100. m at 825 and 780. m water depths and (3) Lophelia reefs forming mini-mounds 2-4. m high and 80-100. m width growing on a flat erosional surface at the summit of the bank at 780-750. m water depths. Otherwise, the Castelao Mound Province at the eastern flank of the bank is mainly constituted by cluster of mini-mounds hosting living Lophelia pertusa and Madrepora oculata reefs. These living reefs are detected based on ultra-high resolutions parametric echosounders as mini-mounds with an acoustically transparent interior. Otherwise, semi-buried and exposed mounds are mapped with a combination of multibeam and backscatter images identified by their high strength values and seabed expression. We conclude that the initiation, growth and distribution of cold-water coral mounds on the Galicia Bank have been controlled by the following environmental forcing ...